A three-state language competition model including language learning and attrition - Scialla, Stefano; Liivand, Jens-Kristjan; Patriarca, Marco; Heinsalu, Els (Frontiers in Complex Systems, 2023)
We develop a three-state agent-based language competition model that takes into account the fact that language learning and attrition are not instantaneous but occur over a finite time interval, i.e., we introduce memory in the system. We show that memory effects have a significant impact on the dynamics of language competition. Furthermore, we find that including heterogeneity in the agents' linguistic skills affects the results substantially. We also explore the role of other factors, such as different levels of language learning difficulty, initial population fractions, and daily interaction rates.